Pineapple distribution classification using RGB and fuzzy - Ezrin Tasnim, Abdul Ghani (2010)
The aim of this study is to classify pineapple distribution based on RGB technique and fuzzy logic as classifier. Nowadays, the grading of pineapple for export is using manual inspection is not very effective and will misjudgement due to mistake of classify the maturity index by labour workers. These applications of classifier pineapple maturity index are fully automated by using RGB technique and Fuzzy logic. The RGB color technique is utilized as the extracted features for the pineapple rind. Further, the extracted feature is classified using fuzzy logic system to determine the maturity level of the pineapple and the distribution mean. The result for this project is 89% accuracy in color identification process which can improve the grading pineapple system with this technique